Digital labour and prosumer capitalism: the US matrix (New York, 2015)
"The global dimension of recreational and professional uses of information and communication technologies makes them look universal and almost ahistorical. Aiming to reterritorialize globalized issues, this collection interrogates new forms of digital labour as economic facts and as ideological justifications for the social order, both of which emerged in the United States.